SARS-CoV-2 VARIANTS GENOME ANALYSIS OF INDONESIAN ISOLATES AND THEIR RESPONSES TO AVAILABLE VACCINES - Audah, Kholis Abdurachim; Shaikho, Nasser Mohamed Ghassan Mohamed Adnan; Yurico, Dyana; Jeremy, Michael; Anisa, Amalda Siti (BRIN - Badan Riset dan Inovasi Nasional, 2024)
SARS-CoV-2 is a virus that initially appeared in Wuhan, China, at the end of 2019. In Indonesia, multiple variants of SARS-CoV-2 have been identified, as well as various local variants that are not yet considered to be ‘variants of concern’. Therefore, this investigation is intended to understand the prevalence and epidemiology of the virus, along with detecting the mutations that occur in genes associated with whole-genome-sequences (WGS) isolated in Indonesia. Analyses were performed to investigate SARS-CoV-2 prevalence in Indonesia using data obtained from GISAID.org. Whole-genome sequencing was performed on random samples taken from GISAID.org utilizing the BLAST tool from NCBI. The variants identified in Indonesia are alpha, beta and delta variants, as well as local variants B.1.470 and B.1.466.2. In total there are 9,260 isolated genomes collected in GISAID were located in Indonesia. Using BLAST, the variants were compared with the Wild-Type from Wuhan NC.045512.2. Multiple mutations were observed in the samples. The results from whole-genome sequencing of variants isolated in Indonesia have found that multiple mutations have occurred in genes of the SARS-CoV-2 virus and it caused alterations in the characteristics of the virus and may affect vaccine efficacy.